Pectins and their Manipulation - Seymour, Graham B.; Knox, J. Paul
Pectins are common to the cell walls of higher plants and contribute to many cell wall functions. Cell walls determine the size and shape of cells and, consequently, the integrity and rigidity of plant tissues. In addition, pectins play a role in ion transport and water retention, they determine the pore size of cell walls and they are involved in defence mechanisms against infections by plant pathogens, wounding, and stress (Bacic et al., 1988). The specific functions of pectins in distinct parts of cell walls or plant tissues are strongly influenced by the amount and nature of the pectic molecules present. The structure of pectins is further influenced by enzymatic and chemical modification reactions during the growth of plants, during the ripening and storage of fruits and as a result of the processing of fruits and vegetables. The structure of pectic molecules therefore depends on many parameters and is subject to considerable change. In addition to all these functions in living tissues, pectins are also of commercial interest, as they are used as gelling agents in the manufacture of jams, jellies, marmalades and confectionery and for the stabilisation of acidified dairy drinks (Voragen et al, 1995; May, 2000).
Keywords: PECTINS